THE AGES OF 55 GLOBULAR CLUSTERS AS DETERMINED USING AN IMPROVED $Δ V^{\rm HB}_{\rm TO}$ METHOD ALONG WITH COLOR-MAGNITUDE DIAGRAM CONSTRAINTS, AND THEIR IMPLICATIONS FOR BROADER ISSUES - VandenBerg, Don A.; Brogaard, K.; Leaman, R.; Casagrande, L. (The Astrophysical journal, 2013)
Ages have been derived for 55 globular clusters (GCs) for which Hubble Space Telescope Advanced Camera for Surveys photometry is publicly available. For most of them, the assumed distances are based on fits of theoretical zero-age horizontal-branch (ZAHB) loci to the lower bound of the observed distributions of HB stars, assuming reddenings from empirical dust maps and metallicities from the latest spectroscopic analyses. The age of the isochrone that provides the best fit to the stars in the vicinity of the turnoff (TO) is taken to be the best estimate of the cluster age. The morphology of isochrones between the TO and the beginning part of the subgiant branch (SGB) is shown to be nearly independent of age and chemical abundances. For well-defined color-magnitude diagrams (CMDs), the error bar arising just from the 'fitting' of ZAHBs and isochrones is ≈ ± 0.25 Gyr, while that associated with distance and chemical abundance uncertainties is ∼ ± 1.5-2 Gyr. The oldest GCs in our sample are predicted to have ages of ≈13.0 Gyr (subject to the aforementioned uncertainties). However, the main focus of this investigation is on relative GC ages. In conflict with recent findings based on the relative main-sequence fitting method, which have been studied in some detail and reconciled with our results, ages are found to vary from mean values of ≈12.5 Gyr at [Fe/H] ∼< – 1.7 to ≈11 Gyr at [Fe/H] ∼> –1. At intermediate metallicities, the age-metallicity relation (AMR) appears to be bifurcated: one branch apparently contains clusters with disk-like kinematics, whereas the other branch, which is displaced to lower [Fe/H] values by ≈0.6 dex at a fixed age, is populated by clusters with halo-type orbits. The dispersion in age about each component of the AMR is ∼ ± 0.5 Gyr. There is no apparent dependence of age on Galactocentric distance (Rsub G) nor is there a clear correlation of HB type with age. As previously discovered in the case of M3 and M13, subtle variations have been found in the slope of the SGB in the CMDs of other metal-poor ([Fe/H] ∼< – 1.5) GCs. They have been tentatively attributed to cluster-to-cluster differences in the abundance of helium. Curiously, GCs that have relatively steep 'M13-like' SGBs tend to be massive systems, located at small Rsub G, that show the strongest evidence of in situ formation of multiple stellar populations. The clusters in the other group are typically low-mass systems (with 2-3 exceptions, including M3) that, at the present time, should not be able to retain the matter lost by mass-losing stars due either to the development of GC winds or to ram-pressure stripping by the halo interstellar medium. The apparent separation of the two groups in terms of their present-day gas retention properties is difficult to understand if all GCs were initially ∼20 times their current masses. The lowest-mass systems, in particular, may have never been massive enough to retain enough gas to produce a significant population of second-generation stars. In this case, the observed light element abundance variations, which are characteristic of all GCs, were presumably present in the gas out of which the observed cluster stars formed.